KESIAP-SIAGAAN MASYARAKAT DALAM PENGELOLAAN BENCANA ALAM - Kasus di Si Tellu Tali Urang Jehe - Sugiyanto Sugiyanto (Sosio Konsepsia, 2009)
Familly Social Conditional Research in Disaster Management, constitutes a case research in Si Tellu Tali Urang Jehe district, Pakpak Bharat regency, with the purpose of research : Identified region which convert hazard level, vulnerability and capacity of citizen against hazard risk; acquired description about the alertness of socieh; in management of natural disaster, covers : Pre, Period and After natural disaster; identified the capacity rise need of society in management of natural disaster and this research has the quality of qualitative descriptive. The condition of Pakpak Bharat regency area generally and specially in Si Tellu Tali Urang Jehe district in hilly, so it is sensitive against landslide. Yet from the disaster happened there many times, the society has been able to predict what natural phenomenon will happen in their area,specially flood and landslide. The copacity of family in predicting the natural phenomenon was acquired from experience (Zearing procedd and understanding from the previous incident). Yet the result of understanding is less socialized to next generation. From the observation during thair stay in the area, the society has k11ow11 some points of sensitive location of disaster and the plascement of POSKO (Command Post) if disaster happens. Regional administration respond and his apparatuses of sector instancy in bullding the alertness of the society is high enough, though it is not supported by PORT AB yet. For that, the decree of Pakpak Bharat regent No. 16/2.006 on Februan; 9,2006 in order to be able to be made reference for arrangement of PORTAB.